Balaganjur Geger Bhaya, a Representation of the Phenomenon of Mount Agung Eruption | Balaganjur Geger Bhaya, sebuah Representasi Fenomena Erupsi Gunung Agung - I Komang Widiasa Mang Wid; Ni Ketut Dewi Yulianti (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
The Baleganjur Geger Bhaya percussion is a work that takes the concept or idea from the phenomenon of the eruption of Mount Agung. The process of creating the Balaganjur Geger Bhaya percussion involves a very original concept designed for the first time. The form and structure of this work still uses the Tri Angga concept, identified by the existence of Kawitan, Pengawak, dan Pengecet. The connection between the Balaganjur Geger Bhaya percussion and the eruption of Mount Agung is that it implies a situation of anxiety and fear among the people around MountAgung about the possibility of further eruptions. The situation is implemented into the title of the work